2019
DOI: 10.14302/issn.2643-6655.jcap-19-2764
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Persons with Intellectual Disabilities Through Work/School Alternation: a Positive Case study

Abstract: Entry into the world of work is an important moment for people with disabilities and for their professional inclusion. Using a case study, This research presents the project of school/work alternation carried out with a student with intellectual disability within a supermarket during the frequency of the last year in a higher institute in northern Italy. This study intends to describe the process and highlight the strategies used in this experience. The paper ends with an analysis of the factors that can favou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…There is ample evidence to suggest that the integrity of executive functioning strongly correlated with fluid intelligence [40]. Neuroimaging studies have implicated various brain regions including the anterior cingulate cortex and the dorsolateral prefrontal cortex and their reciprocal projections to other brain regions to be critically associated with executive functioning [28, 31, 33, 35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is ample evidence to suggest that the integrity of executive functioning strongly correlated with fluid intelligence [40]. Neuroimaging studies have implicated various brain regions including the anterior cingulate cortex and the dorsolateral prefrontal cortex and their reciprocal projections to other brain regions to be critically associated with executive functioning [28, 31, 33, 35].…”
Section: Discussionmentioning
confidence: 99%
“…On this scale, higher scores denoted a higher neuropsychological impairment. In a study using in vivo functional neuroimaging Bohon, Weinbach & Lock [31] have indicated that performance on the Wisconsin Card Sorting Test was associated with an increase in metabolic activity in right frontal pole, inferior frontal gyrus and middle frontal gyrus.Scoring for the Trial Making Test [32] was derived from two versions of the test. The first required the examinee to draw a line connecting the numbers 1 through 25 in sequential order, each shown in a plain black circle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation